PENGARUH KEGIATAN PRAKTIK KERJA INDUSTRI DAN MOTIVASI BERORGANISASI TERHADAP KEMAMPUAN PENGUASAAN SOFT SKILLS SISWA SMK ISLAM AL HIKMAH MAYONG JEPARA - Porbaningsih, Andriyati; Indrawati, Cicilia Dyah Sulistyaningrum; Susantiningrum, Susantiningrum (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
The aims of the study were to find: (1) if there was significant effect of internship practical work toward the soft skills mastery of the eleventh grade students of the Office and Administration Department of SMK Islam Al Hikmah Mayong Jepara; (2) if there was significant effect of the students? organizing motivation towards their soft skills mastery; (3) if there was significant effect of both internship practical work and students? organizing motivation toward their soft skills mastery. This study was a quantitative study applying descriptive method. Its population was the eleventh grade students of the Office and Administration Department of SMK Islam Al Hikmah Mayong Jepara in the year of 2012. Its sample was taken through probability sampling is simple random sampling using lottery. It was 37 students of 58 population. The data were collected by distributing questionnaire and documentation. The data were then analyzed by using the technique of double regression analysis, the linear equation of which was ? = 3,422 + 0,293 + 0,430. Based on the research findings, it can be concluded that: (1) there was a positive significant effect of internship practical work toward the soft skills mastery. This was indicated by the value of > or 0,466 > 0,325, in addition by the value of > or 2,886 > 2,042 in the level of significance 5%; (2) there was a positive significant effect of their organizing motivation toward their soft skills mastery. This could be proved by the value of > or 0,448 > 0,325, in addition by the value of > or 2,727 > 2,042 in the level of significance 5%; and (3) there was a positive significant manner together effect of both the internship practical work and students? organizing motivation toward their soft skills mastery. It was shown by the value of > or 9,470 > 3,33 in the level of significane 5%. The relative contribution of internship practical work ) toward the soft skills mastery (Y) was 52,4% and the one of the organizing motivation ) toward their soft skills mastery (Y) was 47,6%. The relative contribution of the internship practical work ) toward their? soft skills mastery (Y) was 18,8% and their organizing motivation ) toward their soft skills mastery (Y) was 17 %.